The effects of dietary soya and crystalline phytoestrogens on the growth, gonad development and histology of farmed abalone, Haliotis midae - Wu, Yu (Rhodes University, Faculty of Science, Department of Ichthyology and Fisheries Science, 2015)
The inclusion of soya as a dietary protein source in the formulated feed, AbfeedÂ® S34 (Marifeed Pty (Ltd), Hermanus) for farmed abalone, Haliotis midae has resulted in larger gonads during reproductive seasons compared to the gonads of abalone fed kelp or diets that included fishmeal as the only main protein source. The aim of this study was to determine if the isoflavones present in the soya were responsible for this increase in gonad size and the subsequent effects on farmed abalone growth. Animals weighing between 40-50 g were fed one of seven isonitrogenous and isoenergetic diets containing either 0, 25, 50 or 100 percent of the soya component of the commercial feed (AbfeedÂ® S34, Marifeed Pty (Ltd), Hermanus) from September 2013 to March 2014. An additional three diets were formulated to include crystalline isoflavone (ISO). These diets were identical to the 0 percent soya diet (i.e. the fishmeal only diet - FM), only ISO was included at the same rate that ISO occurred in the three soya diets. Data were analysed using a multiple forward stepwise regression analysis (MSR) to test the effects of ISO concentration, soya concentration, time, sex, time by concentration interaction and sex by concentration interaction on growth and gonad development and to identify those variables that most contributed to the model. The inclusion of crystalline ISO failed to promote larger gonads and had no effect on abalone growth, while growth and gonad development was dose dependent on soya inclusion rates with sex and time contributing to the models. Mean monthly weight gain in males correlated with increasing soya concentrations (c) (MSR, y = 3.24 + 0.002c, r2 = 0.23, p = 0.03), ranging from 3.11 Â± 0.55 g abalone-1 month-1 to 4.43 Â± 0.46 g abalone-1 month-1, while both male and female monthly length gain was not influenced by soya concentration with an overall mean of 1.62 Â± 0.05 mm abalone-1 month-1 (MSR, p = 0.05 and p = 0.81, respectively). By December, the whole body mass, meat mass and visceral mass in both males and females decreased with increasing soya levels. However, by February, female whole body mass, meat mass and visceral mass positively correlated with soya levels. At the end of the study, male abalone fed FM with soya equivalent to the commercial feed had the highest whole body mass (69.00 Â± 2.48 g abalone-1), meat mass (41.80 Â± 1.12 g abalone-1), visceral mass (9.00 Â± 2.47 g abalone-1) and gonad bulk index (42.70 Â± 9.82 g abalone-1), while females were not influenced by soya concentrations with an overall whole body mass of 63.46 Â± 0.79 g abalone-1. Weight loss was observed in all treatments between February and March, probably due to a spawning event. The moisture content in the meat was not influenced by treatment, however, visceral water loss was effected by both ISO and soya concentration with time and sex contributing to the model. The visceral water loss of females fed graded levels of soya decreased as a function of soya from December to March, and from December to February for males, whereas females fed ISO-enriched diets decreased as a function of ISO concentration (c) at the end of the study from 74.98 Â± 0.88 to 73.10 Â± 0.75 percent (MSR, y = 74.97 "“ 0.0025c, r2 = 0.20, p = 0.048). The inclusion of crystalline ISO had no significant effect on oogenesis in female farmed Haliotis midae, while the distribution of the predominant oocyte stage, stage 7 (second last stage prior to spawning) was dose-dependent in abalone fed increasing soya concentration (c) (MSR, y = 33.38 + 0.03c, r2 = 0.32, F(1, 18) = 8.52, p = 0.01). The increase in stage 7 oocytes in abalone fed FM with soya did not reduce the number of oocytes (44.96 Â± 3.01 oocytes mm-2) present within the lumen, while the number of oocytes (o) in abalone fed the FM-only based diets decreased with increasing abundance of stage 7 oocytes (MSR, y = 58.28 "“ 0.48c, r2 = 0.38, F(1, 18) = 12.51, p = 0.002), possibly due to the increase in size of the oocytes with thicker jelly coats. This study provided evidence that crystalline isoflavone had no influence on abalone gonad development over five months, while soya had a dose-dependent effect on growth, gonad mass and oogenesis in farmed Haliotis midae. Formulated abalone feed could be manipulated at certain times of the year to obtain maximum growth. These implications and further studies were discussed.
Keywords: Haliotis midae; Haliotis midae -- Feeding and feeds; Haliotis midae -- Growth; Haliotis midae -- Histology; Haliotis midae -- Effect of chemicals on; Soybean as feed; Phytoestrogens